PRELIMINARY STUDY ON THE MORPHOMETRIC AND GENETIC OF SHEAT CATFISHES POPULATION (SILURIDAE) FROM THE DOWN STREAM OF MUSI RIVER, SOUTH SUMATRA PROVINCE, INDONESIA - Rudhy Gustiano; Muhammad Fariduddin Ath-Thar; Deni Radona; Sri Sundari; Irin Iriana Kusmini (Indonesian Fisheries Research Journal, 2021)
Sheat catfishes is an economically important species group from open water in Indonesia. As a high demand in the local market, this species group was threatened from overfishing and habitat destruction. For its sustainability, sheat catfishes should have an attention to be conserved and domesticated. Population genetic study has been done to understand the diversity of sheat catfishes as the basic information for its aquaculture program. Objectives of the current study are to identify and characterize the phenotype and genotype of sheat catfishes population at Plaju, Mariana Ulu, Mariana Ilir and Meritai in the down stream of Musi River, South Sumatra Province. Phenotypic analysis based on truss morphometric used eight land-mark on the body of the observed specimens. Ten specimens from each site varying in size were measured with dial caliper with an accuracy of 0.01 mm. Meanwhile, the genetic analysis used PCR-RAPD method using OPA 06, OPA 08, and OPA 12 primers. DNA was extracted from the fin of the observed specimens. Discriminant analysis reflecting in the canonical function of truss morphometric data showed that six morphometric characters (A1, A2, A5, B2, B4, and C4) enabled to separate sheat catfishes population. The population of Mariana Ulu and Mariana Ilir spread on negative of Y axis, separately from population of Plaju and Meritai. The population of Meritai is on negative of the X axis. Genetic analyses found that the population of Mariana Ilir and Meritai have a percentage polymorphism of 22.00% which was higher than the population from Mariana Ulu and Plaju with a percentage of 18%. The population of Mariana Ilir has the highest heterozygosis value of 0.093. Kinship analysis showed that the population from Plaju and Mariana Ilir has the closest distance (0.3463) while the population of Meritai and Plaju has the farthest distance (0.5429).